Semiotic Analysis of Language in Bullying Discourse: Unveiling Structures and Meanings - Farida, NFN; Supardi, NFN; Muchtar, Jumardin (ppjbsip, 2024)
This research delves into the intricate dynamics of bullying by applying a semiotic approach to language analysis, aiming to uncover the inherent structures and meanings embedded in the discourse surrounding bullying. Bullying, a pervasive and complex social phenomenon, demands a nuanced examination of the language employed within its context. Employing semiotic analysis and qualitative research methodology, this study seeks to deconstruct the layers of meaning contained in bullying discourse by understanding the signs and symbols inherent in language. The data for this research were sourced from a diverse array of outlets, including everyday conversations related to bullying. The semiotic analysis was then applied to identify and interpret linguistic signs, encompassing words, phrases, and symbols, thereby elucidating the veiled meanings within the discourse of bullying. The results of the analysis illuminate that language in the context of bullying manifests itself through both verbal and non-verbal signs, collectively shaping structures of power and control. The findings of this study provide valuable insights into the instrumental role of language as a tool for perpetrating bullying and the intricate process of meaning construction within such contexts. Understanding the dynamics of language in social interactions marked by acts of intimidation and humiliation contributes to a broader comprehension of bullying. Acknowledging the intricacies of language in bullying discourse is pivotal for devising effective strategies to address and counteract this prevalent social issue. This research contributes to the ongoing discourse on bullying by underscoring the significance of linguistic analysis in deciphering the layers of meaning within this complex social phenomenon. Ultimately, it calls for a holistic approach that integrates linguistic insights into the broader framework of anti-bullying initiatives, fostering a more comprehensive understanding of the phenomenon. AbsrtakPenelitian ini menggali dinamika rumit perundungan dengan menerapkan pendekatan semiotik terhadap analisis bahasa, bertujuan untuk mengungkap struktur dan makna yang melekat dalam wacana seputar perundungan. Perundungan, sebagai fenomena sosial yang kompleks dan meresap, menuntut pemeriksaan yang mendalam terhadap bahasa yang digunakan dalam konteksnya. Dengan menggunakan analisis semiotik dan metodologi penelitian kualitatif, studi ini berusaha mendekonstruksi lapisan-lapisan makna yang terkandung dalam wacana perundungan dengan memahami tanda dan simbol yang melekat dalam bahasa. Data untuk penelitian ini diperoleh dari berbagai sumber, termasuk percakapan sehari-hari yang terkait dengan perundungan. Analisis semiotik kemudian diterapkan untuk mengidentifikasi dan menafsirkan tanda-tanda linguistik, mencakup kata-kata, frasa, dan simbol, sehingga mengungkap makna terselubung dalam wacana perundungan. Hasil analisis menunjukkan bahwa bahasa dalam konteks perundungan terwujud melalui tanda verbal dan non-verbal, yang secara kolektif membentuk struktur kekuasaan dan kontrol. Temuan studi ini memberikan wawasan berharga tentang peran instrumental bahasa sebagai alat untuk melakukan perundungan dan proses konstruksi makna yang rumit dalam konteks tersebut. Memahami dinamika bahasa dalam interaksi sosial yang ditandai oleh tindakan intimidasi dan penghinaan berkontribusi pada pemahaman yang lebih luas tentang perundungan. Mengakui kerumitan bahasa dalam wacana perundungan sangat penting untuk merancang strategi yang efektif guna menangani dan melawan isu sosial yang meresap ini. Penelitian ini berkontribusi pada wacana yang sedang berlangsung tentang perundungan dengan menekankan pentingnya analisis linguistik dalam menguraikan lapisan makna dalam fenomena sosial yang kompleks ini. Pada akhirnya, penelitian ini menyerukan pendekatan holistik yang mengintegrasikan wawasan linguistik ke dalam kerangka inisiatif anti-perundungan yang lebih luas, mendorong pemahaman yang lebih komprehensif tentang fenomena ini.